1988
DOI: 10.1104/pp.87.4.859
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Processing Sites of an Arabidopsis 2S Albumin and Characterization of the Complete Gene Family

Abstract: The most abundant isoform of the 2S albumin present in seeds of Arabidopsis thaliana has been sequenced and the corresponding gene isolated. Examination of the protein and DNA sequences allows the determination of the exact proteolytic cleavage sites during posttranslational processing. Like other 2S albumins, that of Arabidopsis is made as a prepropeptide. After removal of the signal peptide, the propeptide is cleaved at four other points, giving two subunits linked by a disulfide bridge(s). Comparison of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
144
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(150 citation statements)
references
References 26 publications
6
144
0
Order By: Relevance
“…In oilseed rape [100], castor bean [101], Arabidopsis [102], brazil nut [103] and lupin [104] these have similar structures, the mature proteins consisting of two subunits associated by interchain disulphide bond(s). The small subunits at about 25-40 residues contain region A, and the large Fig.…”
Section: S Storage Proteinsmentioning
confidence: 99%
“…In oilseed rape [100], castor bean [101], Arabidopsis [102], brazil nut [103] and lupin [104] these have similar structures, the mature proteins consisting of two subunits associated by interchain disulphide bond(s). The small subunits at about 25-40 residues contain region A, and the large Fig.…”
Section: S Storage Proteinsmentioning
confidence: 99%
“…For protein gel blotting, we used antibodies for two members of PSI complexes (PsaA and PsaB), three members of PSII complexes (PsbB, PsbD, and OEC33;Jain et al, 1998;Jeong et al, 2003), the photosynthetic and respiratory ATP synthase (AtpB; Inatomi, 1986), RbcS (Krebbers et al, 1988), and Lhcb3 (Jackowski et al, 2001). Our data showed that PsaB, PsbD, RbcS, and Lhcb3 proteins were undetectable in the ptac14-1 mutant, while the levels of PsaA, PsbB, and OEC33 proteins were significantly decreased in the ptac14-1 mutant compared with the wild-type plant, and the accumulation of AtpB was less affected in ptac14-1.…”
Section: Chloroplast Development Is Defective In Ptac14 Mutantsmentioning
confidence: 99%
“…Genomic libraries were constructed from the RUG-AT2 and RUG-ATIO lines as described by Krebbers et al (1988). The RUG-AT2 genomic library, made from a pool of hemizygous and homozygous T2 plants, was used to clone all target plant DNA sequences described in this work.…”
Section: Construction and Screening Of Phage A Genomic Librariesmentioning
confidence: 99%